PENINGKATAN KREATIVITAS DAN PRODUKTIVITAS MELALUI PELATIHAN KERAJINAN DECOUPAGE DAN E-MARKETING - Juhairiah, Siti; Haryadi, Haryadi; Azhari, Muhammad (Jurnal Pengabdian Masyarakat Khatulistiwa, 2023)
ABSTRACTDecoupage craft training at SLBN-2 Palangkaraya aims to increase the creative abilities and productivity of participants, especially teachers, and children with special needs. The hope is that they can develop business opportunities through high-value handicrafts and support the development of independent entrepreneurs. The training was carried out using Purun Grass media, one of the typical tamarind water plants which are widely found in Palangkaraya. In addition to craft training, the participants were also given e-marketing training to market craft products online. The results of the training show an increase in participants' knowledge and skills in decoupage and e-marketing. The increase in general knowledge regarding decoupage reached 100%, while the increase in specific knowledge reached an average of 91.2%. In terms of skills, most of the participants experienced a good improvement. E-marketing training has also yielded positive results, with increased knowledge of the definition of marketing, types of marketplaces, social media, platforms that suit products, and how to create accounts on marketplaces. The indicator of the success of the service is measured by the level of achievement of the output reaching 75%.Keywords: Decoupage, Marketplace, PurunÂ ABSTRAKPelatihan kerajinan decoupage di SLBN-2 Palangkaraya bertujuan meningkatkan kemampuan kreatifitas dan produktivitas peserta, terutama guru dan anak-anak berkebutuhan khusus. Harapannya, mereka dapat mengembangkan peluang bisnis melalui kerajinan bernilai jual tinggi dan mendukung pengembangan wirausaha mandiri. Pelatihan dilakukan dengan menggunakan media purun, salah satu tanaman khas air asam yang banyak terdapat di Palangkaraya. Selain pelatihan kerajinan, para peserta juga diberikan pelatihan e-marketing untuk memasarkan produk kerajinan secara online. Hasil pelatihan menunjukkan peningkatan pengetahuan dan keterampilan peserta dalam decoupage dan e-marketing. Peningkatan pengetahuan umum mengenai decoupage mencapai 100%, sedangkan peningkatan pengetahuan khusus mencapai rata-rata 91,2%. Dalam hal keterampilan, sebagian besar peserta mengalami peningkatan yang baik. Pelatihan e-marketing juga memberikan hasil yang positif, dengan peningkatan pengetahuan mengenai definisi marketing, jenis marketplace, media sosial, platform yang sesuai dengan produk, dan cara membuat akun di marketplace. Indikator keberhasilan pengabdian diukur dari tingkat ketercapaian luaran mencapai 75%.Kata Kunci : Decoupage, Marketplace, Purun